A Bibliometric Analysis and Mapping of On-Line Registration System in Hospital - Erindah Dimisyqiyani; Sedianingsih Sedianingsih; Rizky Amalia Sinulingga; Nurul Azizah (TIJAB (The International Journal of Applied Business), 2020)
This study analyzes the Bibliometric study about online registration at the hospital. This analysis includes statistical information obtained from the Scopus database of 1,456 research journals taken from 1999 to 2019. Keywords verified from the survey result are used to retrieve relevant articles from the database. The result of the study shows that the journal article occupies the top position is "Gefitinib plus the best supportive care in patients previously treated with difficult to cure non-small lung cancer: Results of a multicentre, multicentre randomized, placebo-controlled study (Evaluation of Iressa Survival in Lung Cancer" written by Thatcher N., Chang A ., Parikh P., JR Pereira, Ciuleanu T., Von Pawel J., Thongprasert S., Tan EH, Pemberton K., Archer V., Carroll K with the number of citation 1,852 in 2005. The best author who wrote a journal article related to online registration is Jaffray, DA which donated nine research article publications related to online registration. The institution that most donated  article publications is the University of Toronto, 54 journal articles. The majority of paper publications was dominated by United State with 326 papers. The number of articles written with this theme have increased from year to year, in other words this theme is still a tranding topic to be researched and developed by researchers.